Rural childhoods in Egypt's desert lands - Hanne Kristine Adriansen (Danish Institute for International Studies (DIIS), 2007)
Based on fieldwork in Egypt's desert lands, this paper discusses rural childhoods in an area experiencing rapid social and cultural change. Since 1987, the Egyptian Government has made new villages in the desert as a means to increase agricultural production and solving problems of unemployment. Many settlers move to the Mubarak villages in order to give their children a good start in life. The desert villages are associated with a type of `rural idyll'. The process of settling in the desert impacts upon the children's possible pathways to adulthood and their identities and social relationships. Not only do the children grow up in a different physical context, they are also exposed to new norms, values and behaviour that influences their everyday life and shape their identity. Especially the change from living in large, extended families to living in nuclear families as well as women's new roles impact upon the children's lives. The social contexts shaping the desert childhoods are in some ways more similar to contexts in `developed' countries than in other parts of rural Egypt. The paper ends up by contrasting ideas of rural childhoods in Egypt with those found in `developed' countries.
Keywords: 330; Regionalplanung; Ländlicher Raum; Siedlung; Kinder; Ägypten